WORDS ARE LIFE. WRITTEN MEMORIES IN THE HOSPICE EXPERIENCE: A QUALITATIVE STUDY - Pieralba Chiarlone; Silvio Giono-Calvetto; Flavia Lena; Gaetano Giuseppe Saita; Roberta Maci; Giovanni Moruzzi; Salvatore Bonanno (Journal of Cancer Rehabilitation)
Background From its inception, palliative care has recognized the vital importance of integrating the spiritual and human dimensions into the care of patients facing serious illness. Writing can become a useful tool for expressing and trying to find meaning in the experience of living through illness and the end of life. In the period 2010-2022, 13 notebooks were made available within the Hospice Kairos in Siracusa, Italy, to patients, caregivers, operators and volunteers so that they could freely write down their thoughts, one per year. The impressive quantity of collected texts constitutes a precious heritage of evidence that deserves to be investigated. Materials and Method The Hospice Notebooks are a collection that includes 575 texts in Italian in prose or poetry which are the subject of the analysis work presented. To proceed with the analysis of the words, we decided to use a qualitative research model based on Grounded Theory because of its flexible characteristics, which are well suited to applied qualitative studies that aim to synthesise data to answer pre-identified research questions. Results This study presents the results of the first stage of the work, in which we quantified word repetition and analysed the representativeness of words with higher redundancy, comparing them over the two decades. The quantitative analysis allowed us to detect that the two most frequently used words were life and thank you: undoubtedly two words with a positive connotation that is confirmed over time, while negative words such as suffering, illness, death and pain are used less overall. Conclusions The blank pages inside the diaries allowed patients and caregivers to express their subjectivity in relation to profound experiences such as illness and death, with absolute stylistic and semantic freedom. This work is only the beginning of a journey of interpretation of the texts, but, despite all the limitations, we believe that provides an unusual image of the hospice experience.